A production process of a wedge for cleaning-free aluminum wire bonding and the wedge produced
By using surface pretreatment and surface strengthening treatment in the production process of aluminum wire bonding, a tight deposition layer is formed, which solves the problem of aluminum chips stuck on the cutting head of the cutting knife, and the cleaning effect of the cutting knife is achieved, improving hardness and wear resistance, and extending the service life.
Patent Information
- Application Number
- CN202111648470.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-29
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2041-12-29
AI Technical Summary
The existing aluminum wire bonding chopper is prone to produce crushed aluminum chips during high-frequency vibration, resulting in adhesion of substances on the surface of the chopper cutting head, affecting the welding effect, and requiring regular cleaning, affecting production efficiency.
The production process of cutting knives for non-cleaning aluminum wire bonding is adopted, including surface pretreatment and surface strengthening treatment. The surface pretreatment steps include ultrasonic cleaning using an alkaline mixture and ethanol, fiber laser structure roughening and sodium hydroxide melt soaking to remove oil stains and oxide layers. The surface reinforcement treatment steps include vapor deposition and heat treatment to form a tight deposition layer to improve the hardness and wear resistance of the chopper.
By increasing the bonding strength between the surface of the splitter knife and the deposited layer, and preventing the broken aluminum chip from adhesion, the cleaning effect of the splitter knife is achieved, extending the service life and improving production efficiency.
Smart Images

Figure BDA0003443460630000121
Abstract
Description
Technical Field
[0001] The present application relates to the field of semiconductor packaging, and more specifically, to a production process of a splitter for cleaning-free aluminum wire bonding and the splitter produced. Background Art
[0002] Aluminum wire bonding splitter is a bonding device used for ultrasonic welding machine auxiliary welding. The ultrasonic generator in the ultrasonic welding machine transmits ultrasonic signals, which are converted into high-frequency vibrations by the transducer. The high-frequency vibrations are transmitted to the splitter through the amplitude transformer. When the splitter contacts the aluminum wire and the welded part, the surface of the welded part and the surface of the aluminum wire rub against each other, causing the aluminum wire and the welded part to be in close contact, forming a firm mechanical connection.
[0003] When the high-frequency vibrating splitter rubs against the aluminum wire and the welded parts, it is easy to cause aluminum chips to form on the surface of the aluminum wire and the welded parts. The aluminum chips adhere to the surface of the splitter head, affecting the next use of the splitter and making it difficult to align the splitter head with the lead wire and the welded parts. Therefore, after the splitter has welded 50,000 points, it is necessary to remove the splitter, clean it with alkaline liquid, rinse it with clean water, and blow it dry before continuing to use it, which affects production efficiency. Summary of the invention
[0004] In order to provide a wedge knife for no-clean aluminum wire bonding, the present application provides a production process of the wedge knife for no-clean aluminum wire bonding and the produced wedge knife.
[0005] In a first aspect, the present application provides a production process for a cleaning-free aluminum wire bonding wedge, which adopts the following technical solution:
[0006] A production process of a cleaning-free aluminum wire bonding wedge, comprising the following steps:
[0007] Preparation of cleaver substrate;
[0008] Surface pretreatment: clean the splitter substrate with an alkaline mixture at 50-60°C, then clean the splitter substrate with ethanol at 22±3°C, and dry; perform fiber laser structure roughening on the dried splitter substrate, and spray cool; immerse the blade of the splitter substrate in molten sodium hydroxide at 70-90°C for 30-60 minutes, cool, clean with ethanol, and dry;
[0009] The alkaline mixed solution comprises the following raw materials in parts by weight: 10-20 parts by weight of an aqueous sodium hydroxide solution with a mass fraction of 18-25% and 3-7 parts of alkylphenol polyoxyethylene ether;
[0010] The surface is strengthened to obtain a splitting knife.
[0011] By adopting the above technical scheme, in the surface pretreatment, the splitter substrate is first ultrasonically cleaned with an alkaline mixed solution, and the alkali in the sodium hydroxide aqueous solution in the alkaline mixed solution reacts with the oil to achieve the purpose of removing the surface oil, so as to improve the bonding strength between the deposited layer and the splitter substrate. When the sodium hydroxide aqueous solution is added, the alkylphenol polyoxyethylene ether is added at the same time, so that the oil on the substrate surface that has not undergone saponification reaction can be dissolved. By using the sodium hydroxide aqueous solution and the alkylphenol polyoxyethylene ether in combination, the surface oil can be removed while the surface oxide layer is removed, and the bonding strength between the surface of the splitter substrate and the deposited layer is improved, so that the splitter can achieve the effect of no need to be cleaned. By controlling the temperature condition at 50-60°C, the decomposition of the alkylphenol polyoxyethylene ether can be avoided while improving the degreasing efficiency.
[0012] Ethanol ultrasonic cleaning is performed at 22±3℃. Ethanol can not only remove the surface oil stains of the splitter substrate, but also no water marks will appear after drying, which improves the bonding strength between the splitter substrate surface and the deposited layer. The evaporation rate of ethanol can be controlled by reducing the temperature from 50-60℃ to 20-23℃.
[0013] After drying, fiber laser structure coarsening is performed to increase the surface roughness of the substrate. The deposited particles grow in these irregular structures and can form a mechanical lock with the substrate. The greater the surface roughness of the substrate, the stronger the mechanical lock effect. At the same time, the increase in roughness increases the contact area between the deposited layer and the substrate, so the bonding strength between the deposited layer and the substrate surface can be further improved. At the same time, the local high temperature generated by the laser action will also cause the cobalt inside and on the surface of the splitter substrate to undergo an oxidation reaction, thereby forming cobalt oxide on the surface of the splitter substrate, which is beneficial to the later decobalting.
[0014] The blade head of the splitter substrate is immersed in molten sodium hydroxide and ultrasonically cleaned with ethanol to achieve the purpose of decobalting. Decobalting the splitter substrate is conducive to the nucleation growth of deposition and improves the bonding strength between the deposition layer and the surface of the splitter substrate. Ethanol cleaning can keep the surface of the splitter substrate free of pollution and further improve the bonding strength between the deposition layer and the surface of the splitter substrate, thereby preventing aluminum chips from adhering to the splitter blade head and achieving the purpose of no cleaning.
[0015] Preferably, the weight ratio of the alkylphenol polyoxyethylene ether to the sodium hydroxide aqueous solution is 1:(3-5).
[0016] By adopting the above technical scheme, by adjusting the weight ratio of alkylphenol polyoxyethylene ether and sodium hydroxide aqueous solution, the degreasing and oxidation layer effects on the substrate surface are improved, the quality of the deposited layer attached to the splitter substrate is further improved, and the bonding strength between the deposited layer and the surface of the splitter substrate is further enhanced, thereby preventing broken aluminum chips from adhering to the splitter head and achieving the purpose of no cleaning.
[0017] Preferably, the fiber laser structure roughening is to process the wedge substrate into a micron-level structure, with a laser scanning speed of 800-1000 mm / s, a scanning interval of 2-20 μm, and a variable step length of 90-100 mm / s.
[0018] By adopting the above technical solution and adjusting the conditions of the fiber laser structure, the surface roughening effect of the splitter substrate is improved, thereby improving the bonding strength between the substrate surface and the deposited layer, preventing aluminum chips from adhering to the splitter head, and making the splitter achieve the effect of no need for cleaning.
[0019] Preferably, the surface strengthening treatment is specifically performed as follows: under the conditions of 5-10MPa and 1020-1200°C, argon, hydrogen and carbon source gas are introduced successively or simultaneously, and the blade head of the pre-treated surface layer of the splitting knife substrate is subjected to vapor deposition. When the dust accumulation thickness reaches 3-5μm, the deposition is stopped and the temperature is lowered to obtain the splitting knife.
[0020] By adopting the above scheme, a deposition layer is formed and heat treatment is performed after the deposition is stopped, which can effectively solve the problems of deposition layer arching and surface cracking, improve the quality of the deposition layer on the surface of the splitting cutter substrate, prevent aluminum chips from adhering to the splitting cutter head, and extend the service life of the splitting cutter by making the splitting cutter free of cleaning.
[0021] Preferably, in the surface strengthening treatment, the carbon source gas is introduced at a flow rate of 40-50 sccm at 850-900°C, and the flow rate of the carbon source gas is reduced to 20-30 sccm after nucleation.
[0022] Furthermore, during the surface strengthening treatment, argon gas is introduced at a flow rate of 30-40 sccm, and the pressure is adjusted to 1-5 MPa, and then argon gas is introduced at a flow rate of 20-25 sccm, and the pressure is adjusted to 0.1-1 MPa.
[0023] Furthermore, in the surface strengthening treatment, hydrogen is introduced at a flow rate of 30-40sccm, an arc is emitted, and after the arc is stable, the hydrogen flow rate is reduced to 20-25sccm. Further, the surface strengthening treatment is specifically performed as follows: under the conditions of 5-10MPa and 1020-1200°C, argon is introduced at a flow rate of 30-40sccm, the pressure is adjusted to 1-5MPa, argon is introduced at a flow rate of 20-25sccm, the pressure is adjusted to 0.1-1MPa, hydrogen is introduced at a flow rate of 30-40sccm, an arc is emitted, and after the arc is stable, the hydrogen flow rate is reduced to 20-25sccm, a carbon source gas is introduced at a flow rate of 40-50sccm under the conditions of 850-900°C, and the carbon source gas flow rate is reduced to 20-30sccm after nucleation, and vapor deposition is performed on the blade head of the pre-treated surface layer of the splitting knife substrate, the dust accumulation thickness reaches 3-5μm, the deposition is stopped, the temperature is lowered, and the splitting knife is obtained.
[0024] By adopting the above technical solution, during the surface strengthening treatment, argon is introduced in stages to avoid argon stratification and improve the role of argon as a protective gas in the vapor deposition process. Hydrogen is added as a reaction gas. On the one hand, it forms atomic hydrogen or ionic hydrogen, which has an etching effect during the material growth process and is beneficial to the diffusion of the reaction gas; on the other hand, it can cause the hydrogen on the surface or inside of the deposited layer to undergo a dehydrogenation reaction, thereby improving the quality of the deposited layer. In addition, hydrogen and argon can be used as carrier gases to improve the stability of gas flow, facilitate the diffusion of reactants, make the deposited layer more uniform, and prevent broken aluminum chips from adhering to the blade head of the splitter, thereby achieving the purpose of no cleaning.
[0025] Under high temperature conditions of 850-900℃, carbon source gas is introduced and decomposed under the catalytic effect of the growth substrate. The gaseous carbon source is cracked at high temperature to generate a large amount of carbon-containing groups and atomic oxygen, which are deposited on the substrate surface under the joint action of the carbon-containing groups and atoms to form diamond nuclei. The nuclei continue to grow, forming a deposition layer on the surface of the splitter substrate, effectively preventing aluminum chips from sticking to the splitter head, so that the splitter for aluminum wire bonding can achieve the effect of no need to clean.
[0026] Preferably, in the surface strengthening treatment, heat treatment is performed after the deposition is stopped.
[0027] By adopting the above technical solution and performing heat treatment after stopping deposition, the bonding strength between the deposited layer and the surface of the splitter substrate can be improved.
[0028] Preferably, the heat treatment temperature is 400-600° C. and the heat treatment is performed for 2-6 hours.
[0029] By adopting the above technical solution, the temperature conditions, time and cooling rate of the surface heat treatment are adjusted to prevent the deposition layer from bulging and cracking, and improve the bonding strength between the deposition layer and the surface of the splitter substrate, thereby preventing aluminum chips from adhering to the splitter head, thereby achieving the purpose of no cleaning.
[0030] Preferably, during the surface strengthening treatment, the cooling rate is 20-40°C / min.
[0031] By adopting the above scheme, by adjusting the cooling rate, it is avoided that the cooling rate is too fast, which causes the deposition layer and the surface of the splitting knife substrate to be loosely bonded, and the bonding strength between the surface of the splitting knife substrate and the deposition layer is improved, thereby improving the hardness of the splitting knife, preventing the splitting knife head from sticking to broken aluminum chips, and making the splitting knife achieve the effect of no need to clean.
[0032] Preferably, the preparation of the splitter substrate comprises mixing the splitter raw materials, stirring and ball milling, drying and granulating to a particle size of 0.1-1.5 μm, injection molding, standing to obtain a blank, degreasing, drying, sintering, and cooling to obtain the splitter substrate.
[0033] In the second aspect, the splitting knife produced by the production process of the no-clean aluminum wire bonding splitting knife described in the present application comprises the following raw materials in parts by weight: 70-80 parts of aluminum oxide, 5-9 parts of chromium carbide, 4-5 parts of zirconium oxide, 2-4 parts of polyacrylamide, 1-3 parts of ammonium citrate and 3-5 parts of titanium dioxide.
[0034] Further, in parts by weight, aluminum oxide can be used in 70 parts, 70-72 parts, 72 parts, 72-74 parts, 74 parts, 74-76 parts, 76 parts, 76-78 parts, 78 parts, 78-80 parts and 80 parts, and more preferably 76 parts; chromium carbide can be used in 5 parts, 5-6 parts, 6 parts, 6-7 parts, 7 parts, 7-8 parts, 8 parts, 8-9 parts and 9 parts, and more preferably 7 parts; zirconium oxide can be used in 4 parts, 4-4.2 parts, 4.2 parts, 4.2-4.4 parts, 4.4 parts, 4.4-4.6 parts, 4.6 parts, 4.6-4.6 parts. 8 parts, 4.8 parts, 4.8-5 parts and 5 parts, more preferably 4.6 parts; polyacrylamide can be used in 2 parts, 2-2.5 parts, 2.5 parts, 3 parts, 3-3.5 parts, 3.5 parts, 3.5-4 parts and 4 parts, more preferably 3 parts; ammonium citrate can be used in 1 part, 1-1.5 parts, 1.5 parts, 1.5-2 parts, 2 parts, 2-2.5 parts, 2.5-3 parts and 3 parts, more preferably 2 parts; titanium dioxide can be used in 3 parts, 3-3.5 parts, 3.5 parts, 3.5-4 parts, 4 parts, 4-4.5 parts, 4.5 parts, 4.5-4 parts and 5 parts.
[0035] By adopting the above technical scheme, alumina has a compact structure, low activity, good chemical stability, high strength and hardness, and good mechanical properties at high temperatures. Adding zirconium oxide and chromium carbide on the basis of adding alumina can make the molecular structure of the splitter more compact, reduce brittleness, have very excellent mechanical properties, and have good biocompatibility, thereby improving the wear resistance, compressive strength and toughness of the splitter. In addition, chromium carbide can prevent the uneven growth of aluminum oxide, hafnium oxide and chromium oxide during the sintering process, thereby increasing the hardness of the splitter and further improving the wear resistance of the splitter. Ammonium polyacrylate can disperse aluminum oxide, hafnium oxide and chromium oxide, but it is easy to cause larger pores after dispersion; while ammonium citrate can promote the discharge of bubbles, and at the same time, it can also play a dispersing role, improve the density of the splitter after sintering, thereby improving the wear resistance of the splitter. Adding titanium dioxide can reduce the sintering temperature of the splitter substrate, increase the activity of the splitter raw material, and promote sintering.
[0036] In summary, the present application includes at least one of the following beneficial technical effects:
[0037] (1) This application adopts the production process of the no-clean aluminum wire bonding splitter and the type and dosage of raw materials selected to achieve a material removal amount of 342.5 mm 3The bending strength is 1042MPa, the deposition bonding force is HF2, the deposition layer is continuous and tight, the surface is smooth and flat, it has high wear resistance and bending strength, and the deposition layer has a high bonding strength with the surface of the splitting knife substrate, which effectively prevents aluminum chips from sticking to the splitting knife head, so that the splitting knife can achieve the effect of no need to clean.
[0038] (2) This application adjusts the laser scanning speed during the fiber laser structure roughening in the surface pretreatment to make the material removal amount of the wedge 317.7mm 3 The bending strength is 1158MPa, the deposition bonding force is HF1, the deposition layer is continuous and tight, and the surface is smooth and flat, which further improves the wear resistance and bending strength of the splitter. At the same time, the deposition layer has a high bonding strength with the surface of the splitter substrate, which effectively prevents the broken aluminum chips from sticking to the splitter head, so that the splitter can achieve the effect of no need to clean.
[0039] (3) The present application controls the temperature of methane (carbon source gas) introduced during the surface strengthening treatment to make the material removal amount of the splitter 269.8 mm 3 The bending strength is 1462MPa, the deposition bonding force is HF1, the deposition layer is continuous and tight, and the surface is smooth and flat, which further improves the wear resistance and bending strength of the splitting knife. At the same time, the deposition layer has a high bonding strength with the surface of the splitting knife substrate, which effectively prevents the broken aluminum chips from sticking to the splitting knife head, so that the splitting knife can achieve the effect of no need to clean.
[0040] (4) The present application controls the temperature of the heat treatment during the surface strengthening treatment to make the material removal amount of the splitter 256.3 mm 3 The bending strength is 1589MPa, the deposition bonding force is HF1, the deposition layer is continuous and tight, and the surface is smooth and flat, which further improves the wear resistance and bending strength of the splitter. At the same time, the deposition layer has a high bonding strength with the surface of the splitter substrate, which effectively prevents the broken aluminum chips from sticking to the splitter head, so that the splitter can achieve the effect of no need to clean.
[0041] (5) This application controls the cooling rate during the surface strengthening treatment to make the material removal amount of the splitter 246.7mm 3 The bending strength is 1632MPa, the deposition bonding force is HF1, the deposition layer is continuous and tight, the surface is smooth and flat, and it has excellent mechanical properties. It can effectively prevent aluminum chips from sticking to the chopper head, making the chopper free of cleaning. DETAILED DESCRIPTION
[0042] The present application is further described in detail below in conjunction with specific embodiments.
[0043] The following raw materials in this application are all commercially available products, and are intended to make the raw materials of this application fully disclosed, and should not be understood as limiting the source of the raw materials. Specifically: Alumina is selected from Shanghai Xiaohuang Nano Technology Co., Ltd., with a particle size of 5μm; Chromium carbide is selected from Hebei Yirui Alloy Welding Materials Co., Ltd., with a particle size of 200 mesh; Zirconium oxide is selected from Shandong Hui'an Chemical Co., Ltd., model JC-R50Y3, with a particle size of 50nm; Polyacrylamide is selected from Henan Yuzhiyuan Water Treatment Materials Co., Ltd.; Ammonium citrate is selected from Jinan Huijinchuan Trading Co., Ltd.; Titanium dioxide is selected from Nanjing Baoket New Materials Co., Ltd., with a particle size of 10nm; Carbon source gas, methane is selected.
[0044] Example 1
[0045] The no-clean aluminum wire bonding wedge of Example 1 is obtained by the following steps:
[0046] Preparation of a splitter substrate: 7600g of aluminum oxide, 700g of chromium carbide and 460g of zirconium oxide were mixed, stirred and ball-milled, dried and granulated to a particle size of 1μm, powder material B was poured into a mold at 60°C, and allowed to stand at 23°C for 2h to obtain a blank, which was soaked in a n-hexane solution for 45min and dried; then soaked in ether for 45min, dried, and then soaked in acetone for 45min and dried; the blank was heated at 0.2MPa and 900°C at a heating rate of 10°C / min to 1000°C, stayed for 3min, and cooled to 23°C to obtain a splitter substrate;
[0047] Surface pretreatment: 1800 g of 25% sodium hydroxide aqueous solution and 300 g of alkylphenol polyoxyethylene ether were mixed to obtain an alkaline mixed solution for standby use;
[0048] At 50°C, the splitting knife substrate was cleaned with an alkaline mixture, and then at 23°C, the splitting knife substrate was cleaned with ethanol and dried; the dried splitting knife substrate was subjected to fiber laser structure roughening, with a laser scanning speed of 1000mm / s, a scanning interval of 2μm, a step size of 100mm / s, and spray cooling; then, the sodium hydroxide solid was heated to a molten state at 450°C to obtain a melt; at 80°C, the blade head of the splitting knife substrate was immersed in the melt for 45min, cooled, cleaned with ethanol, and dried; surface strengthening treatment: at 5MPa and 1200°C, argon, hydrogen and methane (carbon source gas) with a volume ratio of 1:30:1 were introduced at a flow rate of 30sccm at the same time, and the blade head of the splitting knife substrate after surface pretreatment was deposited. After stopping the deposition, the temperature was lowered at a rate of 50°C / min to obtain a splitting knife.
[0049] Example 2
[0050] The cleaning-free aluminum wire bonding wedge of Example 2 is obtained by the following operation steps:
[0051] Preparation of a splitter substrate: 7600 g of aluminum oxide, 700 g of chromium carbide, 460 g of zirconium oxide, 300 g of polyacrylamide, 200 g of ammonium citrate and 500 g of titanium dioxide were mixed, stirred and ball-milled, and the subsequent operations were the same as in Example 1;
[0052] Surface pretreatment: same as in Example 1;
[0053] Surface strengthening treatment: same as in Example 1.
[0054] Example 3
[0055] The no-clean aluminum wire bonding wedge of Example 3 is obtained by the following operation steps:
[0056] Preparation of the wedge substrate: same as in Example 2;
[0057] Surface pretreatment: 1200g of 25% sodium hydroxide aqueous solution and 400g of alkylphenol polyoxyethylene ether were mixed to obtain an alkaline mixed solution for standby use; the remaining operations were the same as those in Example 2;
[0058] Surface strengthening treatment: same as in Example 2.
[0059] Example 4
[0060] The no-clean aluminum wire bonding wedge of Example 4 is obtained by the following operation steps:
[0061] Preparation of the wedge substrate: same as in Example 2;
[0062] Surface pretreatment: 2000g of 25% sodium hydroxide aqueous solution and 500g of alkylphenol polyoxyethylene ether were mixed to obtain an alkaline mixed solution for standby use; the remaining operations were the same as those in Example 2;
[0063] Surface strengthening treatment: same as in Example 2.
[0064] Example 5
[0065] The no-clean aluminum wire bonding wedge of Example 5 is obtained by the following operation steps:
[0066] Preparation of the wedge substrate: same as in Example 2;
[0067] Surface pretreatment: 1500g of 25% sodium hydroxide aqueous solution and 300g of alkylphenol polyoxyethylene ether were mixed to obtain an alkaline mixed solution for standby use; the remaining operations were the same as those in Example 2;
[0068] Surface strengthening treatment: same as in Example 2.
[0069] Example 6
[0070] The no-clean aluminum wire bonding wedge of Example 6 is obtained by the following operation steps:
[0071] Preparation of the wedge substrate: same as in Example 2;
[0072] Surface pretreatment: 1400g of 25% sodium hydroxide aqueous solution and 700g of alkylphenol polyoxyethylene ether were mixed to obtain an alkaline mixed solution for standby use; the remaining operations were the same as those in Example 2;
[0073] Surface strengthening treatment: same as in Example 2.
[0074] Example 7
[0075] The no-clean aluminum wire bonding wedge of Example 7 is obtained by the following operation steps:
[0076] Preparation of the wedge substrate: same as in Example 4;
[0077] Surface pretreatment: same as in Example 4;
[0078] The splitter substrate was cleaned with an alkaline mixed solution at 50°C, and then cleaned with ethanol at 23°C and dried; the dried splitter substrate was roughened with a fiber laser, with a laser scanning speed of 800 mm / s, a scanning interval of 2 μm, and a step length of 100 mm / s. The subsequent operations were the same as those in Example 4;
[0079] Surface strengthening treatment: same as Example 4.
[0080] Example 8
[0081] The no-clean aluminum wire bonding wedge of Example 8 is obtained by the following operation steps:
[0082] Preparation of the wedge substrate: same as in Example 4;
[0083] Surface pretreatment: same as in Example 4;
[0084] The splitter substrate was cleaned with an alkaline mixed solution at 50°C, and then cleaned with ethanol at 23°C and dried; the dried splitter substrate was roughened with a fiber laser, with a laser scanning speed of 900 mm / s, a scanning interval of 2 μm, and a step length of 100 mm / s. The subsequent operations were the same as those in Example 4;
[0085] Surface strengthening treatment: same as Example 4.
[0086] Example 9
[0087] The cleaning-free aluminum wire bonding wedge of Example 9 is obtained by the following operation steps:
[0088] Preparation of the wedge substrate: same as in Example 8;
[0089] Surface pretreatment: same as in Example 8;
[0090] The splitter substrate was cleaned with an alkaline mixed solution at 50°C, and then cleaned with ethanol at 23°C and dried; the dried splitter substrate was roughened with a fiber laser, with a laser scanning speed of 900 mm / s, a scanning interval of 10 μm, and a step length of 100 mm / s. The subsequent operations were the same as those in Example 8;
[0091] Surface strengthening treatment: same as Example 8.
[0092] Example 10
[0093] The no-clean aluminum wire bonding wedge of Example 10 is obtained by the following operation steps:
[0094] Preparation of the wedge substrate: same as in Example 8;
[0095] Surface pretreatment: same as in Example 8;
[0096] The splitting substrate was cleaned with an alkaline mixed solution at 50°C, and then cleaned with ethanol at 23°C and dried; the dried splitting substrate was roughened with a fiber laser, with a laser scanning speed of 900 mm / s, a scanning interval of 20 μm, and a step length of 100 mm / s. The subsequent operations were the same as those in Example 8;
[0097] Surface strengthening treatment: same as Example 8.
[0098] Embodiment 11
[0099] The no-clean aluminum wire bonding wedge of Example 11 is obtained by the following operation steps:
[0100] Preparation of the wedge substrate: same as in Example 9;
[0101] Surface pretreatment: same as in Example 9;
[0102] The splitter substrate was cleaned with an alkaline mixed solution at 50°C, and then cleaned with ethanol at 23°C and dried; the dried splitter substrate was roughened with a fiber laser, with a laser scanning speed of 900 mm / s, a scanning interval of 20 μm, and a step length of 95 mm / s. The subsequent operations were the same as those in Example 9;
[0103] Surface strengthening treatment: same as Example 9.
[0104] Example 12
[0105] The no-clean aluminum wire bonding wedge of Example 12 is obtained by the following operation steps:
[0106] Preparation of the wedge substrate: same as in Example 9;
[0107] Surface pretreatment: same as in Example 9;
[0108] The splitter substrate was cleaned with an alkaline mixed solution at 50°C, and then cleaned with ethanol at 23°C and dried; the dried splitter substrate was roughened with a fiber laser, with a laser scanning speed of 900 mm / s, a scanning interval of 20 μm, and a step length of 90 mm / s. The subsequent operations were the same as those in Example 9;
[0109] Surface strengthening treatment: same as Example 9.
[0110] Embodiment 13
[0111] The no-clean aluminum wire bonding wedge of Example 13 is obtained by the following operation steps:
[0112] Preparation of the wedge substrate: same as in Example 11;
[0113] Surface pretreatment: same as Example 11;
[0114] Surface strengthening treatment: under the conditions of 5MPa and 1200℃, argon is introduced at a flow rate of 35sccm, the pressure is adjusted to 1MPa, and then argon is introduced at a flow rate of 20sccm, the pressure is adjusted to 0.1MPa, hydrogen is introduced at a flow rate of 30sccm, and an arc is emitted. After the arc is stable, the hydrogen flow rate is reduced to 20sccm, and methane (carbon source gas) is introduced at a flow rate of 50sccm at 1000℃. After nucleation, the methane (carbon source gas) flow rate is reduced to 30sccm, and deposition is performed on the blade head of the splitting knife substrate after surface pretreatment. After stopping the deposition, the temperature is lowered at 50℃ / min to obtain the splitting knife.
[0115] Embodiment 14
[0116] The no-clean aluminum wire bonding wedge of Example 14 is obtained by the following operation steps:
[0117] Preparation of the wedge substrate: same as in Example 11;
[0118] Surface pretreatment: same as Example 11;
[0119] Surface strengthening treatment: under the conditions of 5MPa and 1200℃, argon is introduced at a flow rate of 35sccm, the pressure is adjusted to 1MPa, and then argon is introduced at a flow rate of 20sccm, the pressure is adjusted to 0.1MPa, hydrogen is introduced at a flow rate of 30sccm, and an arc is emitted. After the arc is stable, the hydrogen flow rate is reduced to 20sccm, and methane (carbon source gas) is introduced at a flow rate of 50sccm at 850℃. After nucleation, the methane (carbon source gas) flow rate is reduced to 30sccm, and deposition is performed on the blade head of the splitting knife substrate after surface pretreatment. After stopping the deposition, the temperature is lowered at 50℃ / min to obtain the splitting knife.
[0120] Embodiment 15
[0121] The no-clean aluminum wire bonding wedge of Example 15 is obtained by the following operation steps:
[0122] Preparation of the wedge substrate: same as in Example 11;
[0123] Surface pretreatment: same as Example 11;
[0124] Surface strengthening treatment: under the conditions of 5MPa and 1200℃, argon is introduced at a flow rate of 35sccm, the pressure is adjusted to 1MPa, and then argon is introduced at a flow rate of 20sccm, the pressure is adjusted to 0.1MPa, hydrogen is introduced at a flow rate of 30sccm, and an arc is emitted. After the arc is stable, the hydrogen flow rate is reduced to 20sccm, and methane (carbon source gas) is introduced at a flow rate of 50sccm under the conditions of 900℃. After nucleation, the methane (carbon source gas) flow rate is reduced to 30sccm, and deposition is performed on the blade head of the splitting knife substrate after surface pretreatment. After stopping the deposition, the temperature is lowered at 50℃ / min to obtain the splitting knife.
[0125] Example 16
[0126] The no-clean aluminum wire bonding wedge of Example 16 is obtained by the following operation steps:
[0127] Preparation of the wedge substrate: same as in Example 15;
[0128] Surface pretreatment: same as Example 15;
[0129] Surface strengthening treatment: under the conditions of 5MPa and 1200℃, argon is introduced at a flow rate of 35sccm, the pressure is adjusted to 1MPa, and then argon is introduced at a flow rate of 20sccm, the pressure is adjusted to 0.1MPa, hydrogen is introduced at a flow rate of 30sccm, and an arc is emitted. After the arc is stable, the hydrogen flow rate is reduced to 20sccm, and methane (carbon source gas) is introduced at a flow rate of 50sccm at 900℃. After nucleation, the methane (carbon source gas) flow rate is reduced to 30sccm, and deposition is performed on the blade head of the splitting knife substrate after surface pretreatment. After stopping the deposition, heat treatment is performed at 400℃ for 4h, and the temperature is reduced at 50℃ / min to obtain the splitting knife.
[0130] Embodiment 17
[0131] The no-clean aluminum wire bonding wedge of Example 17 is obtained by the following operation steps:
[0132] Preparation of the wedge substrate: same as in Example 15;
[0133] Surface pretreatment: same as Example 15;
[0134] Surface strengthening treatment: under the conditions of 5MPa and 1200℃, argon is introduced at a flow rate of 30sccm, adjusted to 1MPa, and then argon is introduced at a flow rate of 20sccm, adjusted to 0.1MPa, and hydrogen is introduced at a flow rate of 30sccm, and an arc is emitted. After the arc is stable, the flow rate of hydrogen is reduced to 20sccm, and methane (carbon source gas) is introduced at a flow rate of 40sccm at 850℃. After nucleation, the flow rate of methane (carbon source gas) is reduced to 30sccm, and deposition is performed on the head of the splitting knife substrate after surface pretreatment. The deposition is stopped, and heat treatment is performed at 500℃ for 4h. The temperature is lowered at a rate of 20℃ / min to obtain the splitting knife.
[0135] Embodiment 18
[0136] The no-clean aluminum wire bonding wedge of Example 18 is obtained by the following operation steps:
[0137] Preparation of the wedge substrate: same as in Example 15;
[0138] Surface pretreatment: same as Example 15;
[0139] Surface strengthening treatment: under the conditions of 5MPa and 1200℃, argon is introduced at a flow rate of 30sccm, adjusted to 1MPa, and then argon is introduced at a flow rate of 20sccm, adjusted to 0.1MPa, and hydrogen is introduced at a flow rate of 30sccm, and an arc is emitted. After the arc is stable, the flow rate of hydrogen is reduced to 20sccm, and methane (carbon source gas) is introduced at a flow rate of 40sccm at 850℃. After nucleation, the flow rate of methane (carbon source gas) is reduced to 30sccm, and deposition is carried out on the head of the splitting knife substrate after surface pretreatment. When the dust accumulation thickness reaches 0.8μm, the deposition is stopped. At 600℃, heat treatment is carried out for 4h, and the temperature is reduced at a rate of 20℃ / min to obtain the splitting knife.
[0140] Embodiment 19
[0141] The no-clean aluminum wire bonding wedge of Example 19 is obtained by the following operation steps:
[0142] Preparation of the wedge substrate: same as in Example 17;
[0143] Surface pretreatment: same as Example 17;
[0144] Surface strengthening treatment: under the conditions of 5MPa and 1200℃, argon is introduced at a flow rate of 30sccm, adjusted to 1MPa, and then argon is introduced at a flow rate of 20sccm, adjusted to 0.1MPa, and hydrogen is introduced at a flow rate of 30sccm, and an arc is emitted. After the arc is stable, the flow rate of hydrogen is reduced to 20sccm, and methane (carbon source gas) is introduced at a flow rate of 40sccm at 850℃. After nucleation, the flow rate of methane (carbon source gas) is reduced to 30sccm, and deposition is carried out on the head of the splitting knife substrate after surface pretreatment. When the dust accumulation thickness reaches 0.8μm, the deposition is stopped. At 600℃, heat treatment is carried out for 4h, and the temperature is reduced at a rate of 30℃ / min to obtain the splitting knife.
[0145] Embodiment 20
[0146] The no-clean aluminum wire bonding wedge of Example 20 is obtained by the following operation steps:
[0147] Preparation of the wedge substrate: same as in Example 17;
[0148] Surface pretreatment: same as Example 17;
[0149] Surface strengthening treatment: under the conditions of 5MPa and 1200℃, argon is introduced at a flow rate of 30sccm, adjusted to 1MPa, and then argon is introduced at a flow rate of 20sccm, adjusted to 0.1MPa, and hydrogen is introduced at a flow rate of 30sccm, and an arc is emitted. After the arc is stable, the flow rate of hydrogen is reduced to 20sccm, and methane (carbon source gas) is introduced at a flow rate of 40sccm at 850℃. After nucleation, the flow rate of methane (carbon source gas) is reduced to 30sccm, and deposition is performed on the splitting knife substrate after surface pretreatment. After stopping the deposition, heat treatment is performed at 600℃ for 4h, and the temperature is reduced at a rate of 40℃ / min to obtain the splitting knife.
[0150] Embodiment 21
[0151] The no-clean aluminum wire bonding wedge of Example 21 is obtained by the following operation steps:
[0152] Preparation of a splitter substrate: 7000 g of aluminum oxide, 500 g of chromium carbide, 400 g of zirconium oxide, 200 g of polyacrylamide, 100 g of ammonium citrate and 300 g of titanium dioxide were mixed, stirred and ball-milled, and the subsequent operations were the same as in Example 19;
[0153] Surface pretreatment: same as Example 19;
[0154] Surface strengthening treatment: same as Example 19.
[0155] Embodiment 22
[0156] The no-clean aluminum wire bonding wedge of Example 22 is obtained by the following operation steps:
[0157] Preparation of a splitter substrate: 8000 g of aluminum oxide, 900 g of chromium carbide, 500 g of zirconium oxide, 400 g of polyacrylamide, 300 g of ammonium citrate and 500 g of titanium dioxide were mixed, stirred and ball-milled, and the subsequent operations were the same as those in Example 19;
[0158] Surface pretreatment: same as Example 19;
[0159] Surface strengthening treatment: same as Example 19.
[0160] Comparative Example 1
[0161] The no-clean aluminum wire bonding wedge of Example 1 is obtained by the following operation steps:
[0162] Preparation of the wedge substrate: same as in Example 1;
[0163] Surface pretreatment: at 50°C, the substrate was cleaned with 1000g of 25% sodium hydroxide aqueous solution, and the rest of the operations were the same as in Example 1;
[0164] Surface strengthening treatment: same as in Example 1.
[0165] Comparative Example 2
[0166] The no-clean aluminum wire bonding wedge of Example 1 is obtained by the following operation steps:
[0167] Preparation of the wedge substrate: same as in Example 1;
[0168] Surface pretreatment: 1000g of 25% sodium hydroxide aqueous solution and 300g of alkylphenol polyoxyethylene ether were mixed to obtain an alkaline mixed solution for standby use;
[0169] The splitter substrate is cleaned with an alkaline mixed solution at 50°C, and then cleaned with ethanol at 23°C and dried; then, solid sodium hydroxide is heated to a molten state at 450°C to obtain a melt; the blade of the splitter substrate is immersed in the melt at 80°C for 45 minutes, cooled, cleaned with ethanol, and dried;
[0170] Surface strengthening treatment: same as in Example 1.
[0171] Performance Testing
[0172] The following testing standards or methods were used to test the performance of the splitters obtained in different Examples 1-22 and Comparative Examples 1-2. The test results are shown in Table 1.
[0173] The bending strength of the splitter was tested by three-point bending method.
[0174] According to JC / T 2345-2015 "Wear Resistance of Fine Ceramics at Room Temperature", the material removal amount per unit tool wear of the splitting knife is tested. The greater the material removal amount, the worse the wear resistance of the splitting knife.
[0175] Deposit layer thickness: Ellipsometry is used to measure the thickness of the deposited layer.
[0176] Adhesion strength of deposited layer: According to the VDI-3198 standard of the German Association of Science and Technology, the adhesion level ranges from HF1 to HF6, and the higher the level, the worse the adhesion.
[0177] Uniformity of deposited layer: 3D laser confocal microscopy is used to test the uniformity of the deposited layer to observe whether the deposited layer is continuous, dense, and whether the surface is smooth and flat.
[0178] Table 1 Performance test results of different splitters
[0179]
[0180] The test results in Table 1 show that the thickness of the deposited layer of the aluminum wire bonding wedge obtained in Examples 1-22 of the present application is 3.0-5.0 μm, the bonding strength of the deposited layer is HF1-HF3, the deposited layer is relatively continuous and tight, and the surface is smooth and flat. At the same time, the minimum material removal amount of the wedge obtained in the present application is 246.7 mm 3 , strong wear resistance; the bending strength of the splitting knife of the present application is up to 1632MPa, which has high bending strength. It can be seen that the splitting knife obtained by the present application has high hardness and wear resistance, and the splitting knife substrate and the deposition layer have high bonding strength, thereby preventing the splitting knife head from sticking to broken aluminum chips, so that the splitting knife achieves the effect of no need to clean.
[0181] In Examples 1-6, the material removal amount of the splitter in Example 4 is 342.5 mm 3 , which are lower than those of Examples 1-3 and 5-6, and have strong wear resistance; the bending strength of Example 4 is 1042MPa, which are higher than those of Examples 1-3 and 5-6, and have high bending strength; and the deposition bonding force of the splitter of Example 4 is HF2, and the bonding strength is better than that of Examples 1-3 and 5-6, and the deposition layer of the splitter is continuous and tight, and the surface is smooth and flat; it shows that when the weight ratio of alkylphenol polyoxyethylene ether to sodium hydroxide aqueous solution in the surface pretreatment alkaline mixed solution is 1:4, the comprehensive performance of the splitter is relatively excellent. It can be seen that the mechanical properties of the splitter can be improved by using chemical vapor deposition to produce a deposition layer on the surface of the splitter substrate, and surface pretreatment is performed before surface strengthening treatment to remove oil, oxide layer and cobalt on the surface of the splitter, which can improve the bonding strength between the deposition layer and the surface of the splitter substrate, and improve the hardness of the splitter head, thereby preventing the splitter head from adhering to broken aluminum chips, thereby obtaining a splitter for aluminum wire bonding that does not require cleaning.
[0182] In Examples 7-8, the material removal amount of the splitter in Example 8 is 317.7 mm 3 , lower than Example 7, with stronger wear resistance; the bending strength of Example 8 is 1158MPa, higher than Example 7, with higher bending strength; and the deposition bonding force of the splitting knife in Example 8 is HF1, and the bonding strength is better than that in Example 7, the deposition layer of the splitting knife is continuous and tight, and the surface is smooth and flat; it shows that when the laser scanning speed is 900mm / s during the roughening of the fiber laser structure in the surface pretreatment, the comprehensive performance of the splitting knife is relatively excellent; it may be because controlling the laser scanning speed can make the deposition particles smaller, which greatly improves the hardness and wear resistance of the deposition layer.
[0183] Examples 9-10: The material removal amount of the splitter in Example 9 is 307.6 mm 3, which is lower than Example 10, and has stronger wear resistance; the bending strength of Example 9 is 1242MPa, which is higher than Example 10, and has higher bending strength; and the deposition bonding force of the splitting knife in Example 9 is HF1, and the bonding strength is better than that in Example 10, the deposition layer of the splitting knife is continuous and tight, and the surface is smooth and flat; it shows that when the scanning spacing is 10μm during the roughening of the fiber laser structure in the surface pretreatment, the comprehensive performance of the splitting knife is relatively excellent; it may be due to the appropriate scanning spacing, which can improve the wear resistance and corrosion resistance of the splitting knife.
[0184] In Examples 11-12, the material removal amount of the splitter in Example 11 is 285.3 mm 3 , which is lower than Example 12, and has strong wear resistance; the bending strength of Example 11 is 1315MPa, which is higher than Example 12, and has higher bending strength; and the deposition bonding force of the splitting knife in Example 11 is HF1, and the bonding strength is relatively excellent. The deposited layer of the splitting knife is continuous and tight, and the surface is smooth and flat; it shows that when the step size of the fiber laser structure coarsening in the surface pretreatment is 95mm / s, the comprehensive performance of the splitting knife is relatively excellent; it may be that adjusting the appropriate step size is more conducive to the structural coarsening of the splitting knife substrate, improving the bonding strength between the deposited layer and the surface of the splitting knife substrate, thereby preventing the splitting knife head from sticking to broken aluminum chips, and achieving the purpose of no cleaning.
[0185] In Examples 13-15, the material removal amount of the splitter in Example 15 is 269.8 mm 3 , lower than Examples 13-14, with stronger wear resistance; the bending strength of Example 15 is 1462MPa, higher than Examples 13-14, with higher bending strength; and the deposition bonding force of the splitting knife in Example 15 is HF1, with excellent bonding strength, the deposited layer of the splitting knife is continuous and tight, and the surface is smooth and flat; this indicates that when methane (carbon source gas) is introduced at 900°C during the surface strengthening treatment, the performance of the splitting knife is more excellent; it may be related to the fact that suitable temperature conditions can improve the stability of the smooth flow of methane (carbon source gas) and make the deposited layer more uniform.
[0186] In Examples 16-18, the material removal amount of the wrecking tool in Example 17 is 256.3 mm 3 , which is lower than that of Example 16 and Example 18, and has strong wear resistance; the bending strength of Example 17 is 1589MPa, which is higher than that of Example 16 and Example 18, and has high bending strength; and the deposition bonding force of the splitting knife in Example 17 is HF1, and the bonding strength is relatively excellent. The deposition layer of the splitting knife is continuous and tight, and the surface is smooth and flat; it shows that when the heat treatment temperature in the surface strengthening treatment is 500°C, the various properties of the splitting knife are relatively excellent. By adjusting the heat treatment temperature, the phenomenon of arching and cracking of the deposition layer is avoided, and the bonding strength between the deposition layer and the surface of the splitting knife substrate is improved, thereby preventing the splitting knife head from sticking to broken aluminum chips, and achieving the purpose of no cleaning.
[0187] In Examples 19-20, the material removal amount of the splitter in Example 19 is 246.7 mm 3 , which is lower than Example 20, and has strong wear resistance; the bending strength of Example 19 is 1632MPa, which is higher than Example 20, and has higher bending strength; and the deposition bonding force of the splitting knife in Example 19 is HF1, and the bonding strength is relatively excellent. The deposition layer of the splitting knife is continuous and tight, and the surface is smooth and flat; it shows that 30℃ / min cooling is most suitable in the surface strengthening treatment, and the various properties of the splitting knife are relatively excellent. It may be that the appropriate cooling rate can improve the bonding strength between the surface of the splitting knife substrate and the bonding layer, thereby improving the hardness of the splitting knife, preventing the splitting knife head from sticking to broken aluminum chips, and making the splitting knife achieve the effect of no cleaning.
[0188] Combining Example 19 with Examples 21-22, the material removal amount of the splitting knives of Examples 21-22 is higher than that of Example 19, and the bending strength is lower than that of Example 19, indicating that the dosage of each raw material of the splitting knives selected in Example 19 is more appropriate, which improves the wear resistance and bending strength of the splitting knives.
[0189] Combining Comparative Examples 1-2 and Example 1, the performance of the splitting knives of Comparative Examples 1-2 is lower than that of the splitting knives of Example 1, indicating that adding alkylphenol polyoxyethylene ether to the alkaline mixed solution in the surface pretreatment and performing fiber laser structural roughening on the splitting knife substrate can improve the comprehensive performance of the splitting knife, improve the wear resistance and hardness of the splitting knife, prevent the splitting knife head from sticking to broken aluminum chips, and make the splitting knife achieve the effect of no need to clean.
[0190] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A production process for a no-clean aluminum wire bonding wedge, characterized in that: It includes the following steps: S1. Preparation of a splitter substrate: mixing the raw materials for the splitter, stirring and ball milling, drying and granulating, the particle size is 0.1-1.5 μm, injection molding, standing to obtain a blank, degreasing, drying, sintering, cooling, and obtaining a splitter substrate; The cleaver substrate comprises the following raw materials in parts by weight: 70-80 parts of aluminum oxide, 5-9 parts of chromium carbide, 4-5 parts of zirconium oxide, 2-4 parts of polyacrylamide, 1-3 parts of ammonium citrate and 3-5 parts of titanium dioxide; S2. Surface pretreatment: clean the splitter substrate with an alkaline mixed solution at 50-60°C, then clean the splitter substrate with ethanol at 22±3°C, and dry; perform fiber laser structure roughening on the dried splitter substrate, and spray cool; immerse the blade of the splitter substrate in molten sodium hydroxide at 70-90°C for 30-60 minutes, cool, clean with ethanol, and dry; The alkaline mixed solution comprises the following raw materials in parts by weight: 10-20 parts by weight of an aqueous sodium hydroxide solution with a mass fraction of 18-25% and 3-7 parts of an alkylphenol polyoxyethylene ether; S3. Surface strengthening treatment: Under the conditions of 5-10MPa and 1020-1200℃, argon, hydrogen and methane are introduced successively or simultaneously to perform vapor deposition on the blade head of the splitting cutter substrate after surface pretreatment. When the dust accumulation thickness reaches 3-5μm, the deposition is stopped and the temperature is lowered to obtain the splitting cutter.
2. The production process of the cleaning-free aluminum wire bonding knife according to claim 1, characterized in that: The weight ratio of the alkylphenol polyoxyethylene ether to the sodium hydroxide aqueous solution is 1: (3-5).
3. The production process of the cleaning-free aluminum wire bonding knife according to claim 1, characterized in that: The fiber laser structure roughening is to process the wedge substrate into a micron-level structure, with a laser scanning speed of 800-1000 mm / s, a scanning interval of 2-20 μm, and a variable step length of 90-100 mm / s.
4. The production process of the cleaning-free aluminum wire bonding knife according to claim 1, characterized in that: In the surface strengthening treatment, heat treatment is performed after the deposition is stopped.
5. The production process of the cleaning-free aluminum wire bonding knife according to claim 4, characterized in that: The heat treatment temperature is 400-600° C., and the heat treatment time is 2-6 hours.
6. The production process of the cleaning-free aluminum wire bonding knife according to claim 1, characterized in that: During the surface strengthening treatment, the cooling rate is 20-40°C / min.
Citation Information
Patent Citations
Ceramic chopper material and preparation method thereof
CN106995308A
Ceramic product and preparation method thereof
CN107686341A